Effect of Activated Carbon Particle Size on Methylene Blue Adsorption Process in Textile Wastewater - Akhmad Masykur Hadi Musthofa; Mindriany Syafila; Qomarudin Helmy (Indonesian Journal of Chemistry, 2023)
Up to 60–70% of the total textile dyes produced are azo dyes. An example of azo dye is methylene blue, which is commonly used in dyeing wool, silk, and cotton. This substance possessed harmful effects on the environment. Therefore, the removal process is mandatory. The adsorption process is a common method for dye removal in wastewater. One innovation to increase adsorption efficiency even further is by reducing adsorbent particle size. To understand the effect of adsorbent particle size on the adsorption process, in this study, granular activated carbon (GAC) was pulverized into powder (PAC) and superfine powder (SPAC). Adsorbent characterizations, isotherm, kinetics, and thermodynamics tests were conducted. Based on this study, surface area, pore volume, and adsorption capacity were increased for smaller adsorbent particle sizes. Isotherm and kinetic analysis showed that there was no difference in the isotherm and kinetic models that applied to each activated carbon, but there was an increase in the isotherm and kinetic coefficient values at smaller particle sizes. Meanwhile, based on the thermodynamic test, there were differences in the dominant adsorption mechanism for each activated carbon. In GAC and SPAC, the dominant adsorption mechanism was electrostatic interactions, while in PAC was van der Waals forces.